2018
DOI: 10.2478/raon-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of genetic variability on the risk of developing malignant mesothelioma

Abstract: BackgroundMalignant mesothelioma is a rare cancer with poor outcome, associated with asbestos exposure. Reactive oxygen species may play an important role in the mechanism of carcinogenesis; therefore, genetic variability in antioxidative defence may modify an individual’s susceptibility to this cancer. This study investigated the influence of functional polymorphisms of NQO1, CAT, SOD2 and hOGG1 genes, gene-gene interactions and gene-environment interactions on malignant mesothelioma risk.Patients and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…No association was also found between SOD2 and CAT polymorphisms and the malignant mesothelioma risk in a study that included 159 Slovenian malignant mesothelioma patients and 122 controls. All the controls were occupationally exposed to asbestos in the asbestos-cement manufacturing plant but did not develop any disease associated with asbestos exposure [102]. However, this study reported an association between NAD(P)H quinone dehydrogenase 1 (NQO1) rs1800566 (p.Pro187Ser) SNP and malignant mesothelioma risk.…”
Section: Genetic Variability In Antioxidative Defence Genesmentioning
confidence: 69%
See 1 more Smart Citation
“…No association was also found between SOD2 and CAT polymorphisms and the malignant mesothelioma risk in a study that included 159 Slovenian malignant mesothelioma patients and 122 controls. All the controls were occupationally exposed to asbestos in the asbestos-cement manufacturing plant but did not develop any disease associated with asbestos exposure [102]. However, this study reported an association between NAD(P)H quinone dehydrogenase 1 (NQO1) rs1800566 (p.Pro187Ser) SNP and malignant mesothelioma risk.…”
Section: Genetic Variability In Antioxidative Defence Genesmentioning
confidence: 69%
“…NQO1 catalyses the reduction of quinones to hydroquinones, thus preventing the formation of free radicals. The carriers of at least one polymorphic NQO1 allele (CT and TT genotypes) had an increased risk of malignant mesothelioma compared to carriers of homozygous wild-type CC genotype [102].…”
Section: Genetic Variability In Antioxidative Defence Genesmentioning
confidence: 99%
“…[9] Both asbestos related diseases and smoking addition show genetic influence. [10,11] In what concerns asbestosis, the development of lung fibrosis is associated with the nodd like receptor 3 (NLRP3) rs35829419 variant allele, while the transforming growth factor (TGFB1) rs2241718 variant allele with decreased risk [12]. Smoking induced lung fibrosis has similar radiological findings with asbestosis, although the histology is distinguished: the characteristic pattern of asbestosis is the initial localization of fibrosis in the bronchiolar wall and peribronchiolar area of the subpleural region of the lung and the presence of the asbestos bodies; fibrosis progressively extends into alveoli, further from the bronchiole.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that in addition to asbestos exposure, genetic factors may also affect the development of asbestos-related diseases (40)(41)(42). This study investigated the influence of NLRP3 rs35829419 and CARD8 rs2043211 polymorphisms on the risk of different asbestos-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these data, the subjects were divided into three groups: low (< 11 fibres/cm 3 -years), medium (11-20 fibres/ cm 3 -years) and high (> 20 fibres/cm 3 -years) asbestos exposure. For patients with MM with no cumulative asbestos exposure data, accurate work history was obtained, and their asbestos exposures were compared with exposures of the group of subjects with known cumulative asbestos exposure and were accordingly divided into three groups with presumed low, medium and high asbestos exposure, as previously described (40). Reliable semi-quantitative data on asbestos exposure could be obtained only for 81 MM patients.…”
Section: Methodsmentioning
confidence: 99%